Health Complications Associated with Anabolic-Androgenic Steroid Use in Physically Active Men: A Literature Review - Kacprzak, Urszula; Biernacka, Zofia; Celmer, Mikołaj; Kossakowska, Julia; Majchrzak, Mateusz; Ruszkowski, Marcin (Journal of Education, Health and Sport, 2026)
Aim. The aim of this study was to review the current scientific literature on the adverse effects of anabolic-androgenic steroids (AAS) use in physically active men and to highlight the need for further research in this field. Introduction. The use of anabolic-androgenic steroids among physically active individuals is an increasing public health concern and is associated with significant health risks. In recent years, the use of these substances has expanded beyond professional athletes to include recreationally active individuals. Methods. A literature review was conducted using the PubMed and Google Scholar databases. The search included studies published between 2017 and 2025 focusing on the health effects of AAS use in physically active men. Results. Analysis of the available literature indicates that supraphysiological doses of AAS are associated with numerous adverse effects. The most significant complications involve the cardiovascular system (including hypertension and atherosclerosis), the endocrine system (particularly suppression of endogenous testosterone production and infertility), and psychiatric health (including mood disorders and increased aggression). Additional complications affecting the liver, kidneys, and skin have also been reported. Discussion. The findings suggest that AAS use poses a serious health risk, particularly due to its multi-system effects and the potential for long-term complications. The increasing prevalence of AAS use among recreational athletes further emphasizes the need for greater clinical awareness and early identification of affected individuals. Conclusion. Increasing awareness of the health risks associated with AAS use among both patients and healthcare professionals is essential for effective prevention and management. Further research is needed to better understand the long-term consequences of AAS use.